Progressive MS Alliance Industry Forum: Maximizing Collective Impact To Enable Drug Development. (October 2016) - Zaratin, P.; Comi, G.; Coetzee, T.; Ramsey, K.; Smith, K.; Thompson, A.; Panzara, M.
Abstract : The Progressive MS Alliance Industry Forum describes a new approach to address barriers to developing treatments for progressive multiple sclerosis (MS). This innovative model promises to facilitate robust collaboration between industry, academia, and patient organizations and accelerate research towards the overarching goal of developing safe and effective treatments for progressive MS.